Transforming leadership a new pursuit of happiness - Burns, James MacGregor 1918-2014 (Atlantic Monthly Press, 2003)
The award-winning historian critically examines the role of leadership in the twenty-first century, outlining a program through which leaders can become agents of positive social change.
Includes bibliographical references and index
Keywords: Empowerment; Politieke leiding; Führung; Geschichte; Leadership; Leadership -- History